O segundo ciclo de planos diretores pós estatuto da cidade: avanços e desafios - Souza, Amanda Paulista de (2021)
Since the approval of Federal Law nº 10.257/2001, which regulated the constitutional provisions on urban policy and provided the institutional and normative apparatus for the formulation of the Master Plans, the first cycle of Master Plans after the City Statute began. Since the years 2010, the second cycle has initiated, due to the mandatory reviews of those who composed the previous cycle. This research aims to focus on this second cycle based on two approaches: the formal approach, which will investigate the adhesion of Brazilian municipalities to the second cycle of Master Plans after the City Statute; and the material approach that, from the analysis of the discipline, instruments and strategies related to the theme of urban expansion in the Master Plans of the second cycle, will investigate possible advances in such legislation in relation to the debates and criticisms drawn up in the Master Plans of the previous cycle, using as a basis Santoro's research (2012). It is concluded that, although the first cycle was characterized by a majority adhesion of the Brazilian municipalities and by the existence of an institutional and normative apparatus of the urban policy oriented to foment and recognize it, such movement has not been observed in the first years the second cycle, which impacts both the formal adhesion of the municipalities and the incorporation of the matters and debates carried out throughout the previous cycle in their legislation.